Master's Students' Perceptions of Instagram for Self-Directed Arabic Learning in the Age of Artificial Intelligence - Anam, Hairul; Sanja Dimyati, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
The increasing use of social media has created new opportunities for self-directed language learning beyond formal classrooms. However, little is known about how postgraduate students perceive Instagram as a medium for self-directed Arabic language learning. This study explores master's students' perceptions of Instagram and identifies its perceived benefits and challenges. A qualitative descriptive approach was employed involving master's students in the Teaching Arabic to Non-Native Speakers program at the International Islamic University Malaysia. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that students generally perceive Instagram positively because it provides flexible access to authentic learning resources, promotes continuous language exposure, and supports learner autonomy. The platform also enhances vocabulary development, listening skills, motivation, and learning flexibility. Nevertheless, digital distractions, fragmented learning content, and varying content quality remain significant challenges, highlighting the importance of self-regulation and digital literacy. This study demonstrates that Instagram's educational value lies in fostering learner autonomy and provides practical insights for integrating social media into Arabic language learning in the AI era.